Th17 Cells Are More Protective Than Th1 Cells Against the Intracellular Parasite Trypanosoma cruzi. - Catherine W Cai; Jennifer R Blase; Xiuli Zhang; Christopher S Eickhoff; Daniel F Hoft (PLoS Pathogens)
Th17 cells are a subset of CD4+ T cells known to play a central role in the pathogenesis of many autoimmune diseases, as well as in the defense against some extracellular bacteria and fungi. However, Th17 cells are not believed to have a significant function against intracellular infections. In contrast to this paradigm, we have discovered that Th17 cells provide robust protection against Trypanosoma cruzi, the intracellular protozoan parasite that causes Chagas disease. Th17 cells confer significantly stronger protection against T. cruzi-related mortality than even Th1 cells, traditionally thought to be the CD4+ T cell subset most important for immunity to T. cruzi and other intracellular microorganisms. Mechanistically, Th17 cells can directly protect infected cells through the IL-17A-dependent induction of NADPH oxidase, involved in the phagocyte respiratory burst response, and provide indirect help through IL-21-dependent activation of CD8+ T cells. The discovery of these novel Th17 cell-mediated direct protective and indirect helper effects important for intracellular immunity highlights the diversity of Th17 cell roles, and increases understanding of protective T. cruzi immunity, aiding the development of therapeutics and vaccines for Chagas disease.